Design, Network Analysis, In silico Modeling and Synthesis of Biologically Active Thiazolo Quinazoline Scaffolds as Anti-tubercular Agent - Theivendren, Panneerselvam; Subramanian, Arumugam; Kunjiappan, Selvaraj; Arunachalam, Sankarganesh; Murugan, Indhumathy; Arumugam, Sivakumar (Current Chemical Biology, 2017)
Background: Mycobacterium tuberculosis (M. tuberculosis), has a long history of association with human life. By evading the immune response it survives inside macrophages as most successful pathogens known today. An important virulence factors for pathogenic mycobacteria has recently been identified to be a eukaryotic-like serine/threonine protein kinase, termed protein kinase G (PknG). Objective: In this connection, the drug target PknG was identified by using KEGG database and network analysis through Cytoscape software. Inhibition of PknG activity leads to a rapid degradation of mycobacteria inside host cells. In this study, eight novel thiazolo [2,3-b] quinazolin-3-phenyl hydrazone (5a-h) derivatives were synthesized and have been docked to the active site of the PknG using Auto- Dock 4.2 program. Method: The free energies of binding (ΔG) and inhibition constants (Ki) of the docked compounds were calculated by the Lamarckian Genetic Algorithm (LGA). Results: These values suggest that compounds 5f, 5c, 5a are excellent inhibitors of PknG, these compounds interact with lysine 181which was a key residue for PknG activity and the synthesized compounds were also screened by in vitro BACTEC 460 radiometric method against M. tuberculosis H37Rv strain at 6.25 μg/mL. Conclusion: The highest inhibition observed with the synthesized compound was 6,7,8,9-tetrahydro- 5H-5-(2'-hydroxyphenyl)-2-(4'-fluorobenzylidene) thiazolo[2,3-b]quinazolin-3-phenylhydrazone 5f.
Keywords: Mycobacterium tuberculosis